Outcomes of primary repair of sternal cleft defects: Providing a "bony cover" - Parashar Jaytesh; Reena K Joshi; Neeraj Aggarwal; Raja Joshi (Wolters Kluwer Medknow Publications, 2022)
Background : Sternal clefts are rare congenital anterior chest wall defects created by a lack of midline thoracic fusion. Various surgical repairs have been proposed to provide protection to underlying viscera in these defects. Aim : This study aims to perform primary sternal cleft repair using techniques, leading to the provision of a complete bony cover and to assess their outcomes on follow-ups. Materials and Methods : During 2009-2020, seven patients were referred to our unit with sternal defects. Out of them, four infants with sternal clefts underwent primary repair using bilateral perichondrial flap creation of the sternal bars and sliding costal chondrotomy at our institute. In one of them with a wider defect, bilateral "intraperiosteal" sliding clavicular osteotomy was additionally performed to achieve tension-free closure. Results : Satisfactory surgical outcomes were achieved with an uneventful postoperative period. On follow-up, all four patients are thriving well and have a stable anterior chest wall. Those with follow-ups longer than 5 years showed evidence of bone formation. Conclusion : Bony cover to the heart can be provided in all varieties of sternal cleft defects using primary surgical repair early in infancy. The delay in surgical correction increases the complexity of the procedure and may require the use of prosthetic material which has its own disadvantages.